Financial Fitness For Young Professionals: From Savings To Investment - Siti Zulaikhah; Hiro Sejati; Dede Supian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the financial behaviors and literacy of young professionals at CIMB Niaga Bank, focusing on savings, investment practices, financial fitness, and financial literacy. A sample of 90 customers was selected using random sampling techniques. Data was collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with Smart PLS software. The results indicate significant direct effects, with savings habits influencing both financial fitness and financial literacy. However, investment practices did not significantly mediate the relationship between investment and financial literacy. These findings underscore the importance of savings behaviors for long-term financial well-being and knowledge acquisition. The study suggests avenues for CIMB Niaga to enhance its support for customers' financial education and well-being, such as integrating savings-focused financial education initiatives and personalized investment guidance. Overall, this research provides insights into the financial behaviors and literacy of young professionals, offering implications for financial institutions and policymakers aiming to promote financial well-being among this demographic.